KEANEKARAGAMAN TANAMAN PEKARANGAN DAN PEMANFAATANNYA DI DESA LAMPEAPI, PULAU WAWONI – SULAWESI TENGGARA - Rahayu, Mulyati (Jurnal Teknologi Lingkungan, 2005)
In Indonesia, home garden have not aequire any much awareness yet. Although this home garden can be a valuable incomes for family if manage in good way. Research and inventory on plant diversity of home garden in Lampeapi village, Wawonii Dictrict, Southwest Of Celebes resulted of 40 species.Those plants are used daily needs and can be used for raising family income such as “onii” Cocos nucifera, “marisa” Piper nigrum, “dambo” Anacardium occidentale, “punti” Musa spp. and coklat Theobroma cacao. Diversity of plants species, as proportion and indigenous knowledge of local people is very interesting to study in order to conserve their germ plasma.